2022
DOI: 10.3389/fmed.2022.828991
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Peripapillary Retinal Nerve Fiber Layer and Macular Ganglion Cell Inner Plexiform Layer in Progressive Myopia and Glaucoma Among Adolescents

Abstract: PurposeThis study aimed to investigate the differences in longitudinal changes in the peripapillary retinal nerve fiber layer (pRNFL) and macular ganglion cell plus inner plexiform layer (GCIPL) caused by progressive myopia and glaucoma among adolescents.DesignThis was a retrospective observational study.MethodsA total of forty-seven and 25 eyes of 47 and 25 adolescents with myopia progression (MP) and glaucoma progression (GP), respectively, who were followed up at the Zhongshan Ophthalmic Center for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, several reports have indicated that postrecovery SARS-CoV-2 patients have a significantly thinner RNFL than healthy individuals [ 18 , 32 , 33 ]. And a reduced RNFL thickness has been linked to an increased risk of various diseases, such as Alzheimer's disease and glaucoma [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several reports have indicated that postrecovery SARS-CoV-2 patients have a significantly thinner RNFL than healthy individuals [ 18 , 32 , 33 ]. And a reduced RNFL thickness has been linked to an increased risk of various diseases, such as Alzheimer's disease and glaucoma [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%